2005
DOI: 10.1021/cm050971j
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Structure-Directing Effect of Fluorine-Containing Organic Molecules and Fluoride Anions in the Synthesis of Zeolites

Abstract: Dibenzyldimethylammonium (DBDM) cations, singly fluorinated at the ortho, meta, and para positions of the aromatic ring, have been investigated as structure-directing agents (SDAs) for the synthesis of all-silica zeolites in fluoride media and compared with the nonfluorinated molecule. The nonfluorinated DBDM cation can direct the synthesis either to an all-silica zeolite beta or to an all-silica zeolite ZSM-50 with the EUO framework topology. Under the same conditions that DBDM gives zeolite beta, benzylortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 27 publications
4
49
1
Order By: Relevance
“…More recently, Luo et al employed dispersion-corrected DFT calculations to predict the energetically preferred fluoride sites in an MWW-type all-silica zeolite. 24 They obtained very similar energies for two fluoride locations in different cages, concluding that the coexistence of two fluoride environments is responsible for the presence of two distinct resonances in the 19 F NMR spectrum.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…More recently, Luo et al employed dispersion-corrected DFT calculations to predict the energetically preferred fluoride sites in an MWW-type all-silica zeolite. 24 They obtained very similar energies for two fluoride locations in different cages, concluding that the coexistence of two fluoride environments is responsible for the presence of two distinct resonances in the 19 F NMR spectrum.…”
Section: Introductionmentioning
confidence: 92%
“…The first observation of such a building unit in the crystal structure of an as-synthesized all-silica zeolite was reported in 1995 for nonasil (NON framework type code 10 ), 11 followed by analogous findings for various other zeolites. [12][13][14][15][16][17][18][19][20][21]22 The body of crystal structure data shows a preference of fluoride to bond to Si atoms that are part of small rings, most typically four-membered rings (4MRs) or, if these are not present in the structure, 5MRs.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[14][15][16][17][18][19][20] This is often due to the difficulties in locating the fluoride ions by XRD, as they are isoelectronic with OH groups that are often present as defects in zeolite frameworks. 21 The local structure of the [SiO 4/2 F] À units reported by XRD, is often not the true local structure but is an average between [SiO 4/2 F] À and SiO 4/2 units, due to the incomplete occupancy of the fluoride ions in the form of either static or dynamic disorder. 22 This disorder often leads to the reporting of an average F-Si bond distance, which is much longer (between 1.84-1.99 Å) than the real distance (1.76-1.78 Å) in the five coordinate species.…”
mentioning
confidence: 99%
“…The F − ions may act as mineralizing agents and catalysts for the formation of Si‐O‐Si bonds during the nucleation, crystallization, and growth of zeolite crystals . In some cases, F − ions play unique structure‐directing roles through strong interactions with the zeolite . When IM‐20‐A was crystallized in the absence of F − ions, only a material with extremely low framework crystallinity was obtained, and an excess of H 2 O or less OSDA both have highly negative influences on the synthesis of highly crystalline IM‐20‐R (Figure S9 and Table S7 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[24,25] In some cases, F À ions play unique structure-directing roles through strong interactions with the zeolite. [26,27] When IM-20-A was crystallized in the absence of F À ions, only amate- rial with extremelyl ow framework crystallinity waso btained, and an excesso fH 2 Oo rl ess OSDA both have highly negative influences on the synthesis of highly crystalline IM-20-R (Figure S9 and Ta bleS7i nt he Supporting Information). Meanwhile, thermogravimetric analysis (TGA) indicated that the OSDA species participated in the crystallization process ( Figure S10 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%